2017
DOI: 10.7567/jjap.56.112503
|View full text |Cite
|
Sign up to set email alerts
|

Millisecond-order X-ray phase tomography with compressed sensing

Abstract: We report on millisecond-order X-ray tomography with grating-based X-ray imaging using a white synchrotron X-ray beam. We performed a compressed sensing technique for tomographic reconstruction and successfully obtained a phase tomogram for a polypropylene sphere with a temporal resolution of 2.0 ms. Our approach will make it possible to realize millisecond-order four-dimensional X-ray tomography but also to markedly reduce the radiation damage of samples including polymer and biological materials, and will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Highly intense synchrotron radiation X-rays can solve this problem [27][28][29][30][31]. The authors succeeded in X-ray CT with an imaging time on the order of milliseconds by using a third-generation synchrotron radiation source and rotating samples at high speed [27][28][29]. The experiments were performed at the experimental station BL28B2 at SPring-8, a large synchrotron radiation facility.…”
Section: Temporal Resoluɵon [S]mentioning
confidence: 99%
See 2 more Smart Citations
“…Highly intense synchrotron radiation X-rays can solve this problem [27][28][29][30][31]. The authors succeeded in X-ray CT with an imaging time on the order of milliseconds by using a third-generation synchrotron radiation source and rotating samples at high speed [27][28][29]. The experiments were performed at the experimental station BL28B2 at SPring-8, a large synchrotron radiation facility.…”
Section: Temporal Resoluɵon [S]mentioning
confidence: 99%
“…To increase the field of view, the so-called offset CT was used: the two projections from opposite directions were combined to obtain a single projection image. Since only 76 projections for a half turn of the sample can be obtained, using the classical CT reconstruction algorithm (filtered back-projection algorithm) results in radial artifacts as shown in the left pad in the figure . A compressed sensing-based CT reconstruction method has recently attracted attention as a solution to this problem [28,[44][45][46][47][48][49]. In this method, images are recovered from a small number of observation data samples by using the inherent sparsity of images.…”
Section: With Compressed Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important for accessing the dynamic information on the lithium cell upon electrochemical cycling. Some recent studies have demonstrated that high speed (0.5 s) and even real-time (2–4.43 ms) X-ray tricontrast imaging can be achieved by using the white or pink synchrotron X-ray beams. The high-throughput tricontrast imaging approach could offer insights into the evolution of the microstructure of the lithium deposit under different cycling conditions.…”
Section: Tricontrast X-ray Radiography On a Capillary Lithium Cellmentioning
confidence: 99%
“…This substantial reduction in flux leads to longer data acquisition times, reduced signal-to-noise ratios and difficulty in achieving high resolution at BL-4. In several scientific and industrial applications, the demand for higher flux density and increased penetration depth in real-time imaging and in situ material testing experiments far outweighs the advantages offered by a ISSN 1600-5775 monochromatic beam (Patterson et al, 2018;Singh et al, 2014;Yashiro et al, 2017;Reinhart et al, 2014;García-Moreno et al, 2018). In fact, for phase-contrast imaging, there is only a moderate requirement of temporal coherence for many advanced phase contrast techniques, such as X-ray speckle imaging, grating-based phase-contrast imaging etc.…”
Section: Introductionmentioning
confidence: 99%